THE CHARACTER VALUE OF THE SEDEKAH BUMI TRADITION IN RACI VILLAGE, BATANGAN SUB-DISTRICT, PATI REGENCY - Hamida, Khoirul; Ardianti, Sekar Dwi; Rondli, Wawan Shokib (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2022)
AbstractThe purpose of this research was to determine the character values of the Sedekah Bumi tradition in Raci Village, Batangan Sub-District, Pati Regency. This research is qualitative research with a case study type-research that will be conducted in Raci Village. The researched object is the Sedekah Bumi Tradition. This research uses observations, interviews, and documentation as the data collection techniques. The results of the research reveal that the Sedekah Bumi Tradition is held on Wednesday (Rabu Wage Bulan Apit of the Javanese Calendar) by conducting rituals and other events at Punden Raci, Punden Ketitang Kulon, Punden Sumur Brumbung, and Pulo Sawahan, where these places are believed to be the tombs of Mbah Danyang as an ancestor in ancient times who had cleared the village land (babad alas Raci Village). The character values that exist in the Sedekah Bumi Tradition are the values of a religious character, tolerance, discipline, love of the motherland, social care, and responsibility. The conclusion of this research is that the Sedekah Bumi tradition is a legacy from our ancestors that is still preserved by the next generation of the nation. The Sedekah Bumi tradition has six positive character values that are well taught to the people of Raci Village and elementary school-age children. Keywords: Sedekah Bumi Traditions; character values.